TMEM165 Deficiency Causes a Congenital Disorder of Glycosylation - Foulquier, François (Elsevier, 2012)
Protein glycosylation is a complex process that depends not only on the activities of several enzymes and transporters but also on a subtle balance between vesicular Golgi trafficking, compartmental pH, and ion homeostasis. Through a combination of autozygosity mapping and expression analysis in two siblings with an abnormal serum-transferrin isoelectric focusing test (type 2) and a peculiar skeletal phenotype with epiphyseal, metaphyseal, and diaphyseal dysplasia, we identified TMEM165 (also named TPARL) as a gene involved in congenital disorders of glycosylation (CDG). The affected individuals are homozygous for a deep intronic splice mutation in TMEM165. In our cohort of unsolved CDG-II cases, we found another individual with the same mutation and two unrelated individuals with missense mutations in TMEM165. TMEM165 encodes a putative transmembrane 324 amino acid protein whose cellular functions are unknown. Using a siRNA strategy, we showed that TMEM165 deficiency causes Golgi glycosylation defects in HEK cells.